Incidence of myocardial injury in patients submitted to carotid endarterectomy: a systematic review - Ana Filipa Fonseca da Silva (2022)
BACKGROUND Myocardial injury following noncardiac surgery (MINS) is associated with higher mortality and major adverse cardiovascular event rates in the short- and long-term in patients undergoing carotid endarterectomy (CEA). However, its incidence is still unclear in this subset of patients. Therefore, this systematic review with meta-analysis aims to determine the incidence of MINS in patients undergoing CEA. MATERIALS AND METHODS Three electronic databases MEDLINE, Scopus, and Web of Science were used to search for studies assessing the occurrence of MINS in the postoperative setting of patients undergoing CEA. The incidence of MINS was pooled by random-effects meta-analysis, with sources of heterogeneity being explored by meta-regression. Additionally, the incidence of MINS regarding subgroups of patients (general anesthesia vs. regional anesthesia) was also analysed. Assessment of studies' quality was performed using National Heart, Lung, and Blood Institute (NHLBI) Study Quality Assessment Tool for Observational Cohorts and Cross-Sectional Studies, and Risk of Bias 2 tools. RESULTS Twenty studies were included, with a total of 117,933 participants. Four of them were randomized controlled trials (RCT), while the remaining were cohort studies. All observational cohorts had an overall high risk of bias, except for Pereira Macedo et al. Three of them had repeated population, thus only data from the most recent one was considered. On the other hand, all RCT had an overall low risk of bias. In patients under regional anesthesia, the incidence of MINS in primary studies ranged between 2% and 15.3%, compared to 0-42.5% for general anesthesia. The meta-analytical incidence of MINS after CEA was of 6.3% [95% CI 2.0%-10.6%], but severe heterogeneity was observed (I2 = 99.1%). CONCLUSION MINS appears to be relatively common among patients undergoing CEA. The observed severe heterogeneity points to the need for further larger studies adopting consistent definitions of MINS and equivalent cut-off values.